2014
DOI: 10.1158/1078-0432.ccr-13-1063
|View full text |Cite
|
Sign up to set email alerts
|

Gambogic Acid Induces Apoptosis in Imatinib-Resistant Chronic Myeloid Leukemia Cells via Inducing Proteasome Inhibition and Caspase-Dependent Bcr-Abl Downregulation

Abstract: Purpose Chronic myelogenous leukemia (CML) is characterized by the constitutive activation of Bcr-Abl tyrosine kinase. Bcr-Abl-T315I is the predominant mutation that causes resistance to imatinib, cytotoxic drugs, and the second-generation tyrosine kinase inhibitors. The emergence of imatinib resistance in patients with CML leads to searching for novel approaches to the treatment of CML. Gambogic acid, a small molecule derived from Chinese herb gamboges, has been approved for phase II clinical trial for cancer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
118
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(122 citation statements)
references
References 46 publications
4
118
0
Order By: Relevance
“…Previous studies have suggested that GA induces cell cycle arrest and apoptosis (7), inhibits the activity of telomerase, angiogenesis and tumor metastasis, and decreases resistance to multiple chemotherapy drugs (8,9). The effect of GA is thought to be highly selective, in one study it was found to induce apoptosis only in tumor cells (10). However, the mechanism of action of GA on tumor cells remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that GA induces cell cycle arrest and apoptosis (7), inhibits the activity of telomerase, angiogenesis and tumor metastasis, and decreases resistance to multiple chemotherapy drugs (8,9). The effect of GA is thought to be highly selective, in one study it was found to induce apoptosis only in tumor cells (10). However, the mechanism of action of GA on tumor cells remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that GA gains the proteasomeinhibitory function after being metabolized by intracellular CYP2E1, that GA induced proteasome inhibition is a prerequisite for its cytotoxicity and anticancer action without off-target effects, and that the expression of the CYP2E1 gene is very high in tumor tissues but low in many normal tissues, and thus GA can produce tissue-specific proteasome inhibition and tumor-specific toxicity (Figure 2). Further, they showed that GA-induced proteasome inhibition and caspase activation are required for GA-induced BCR-ABL downregulation and cell apoptosis [71]. Judging by present reports, most current studies are mainly focused on finding tyrosine kinase inhibitors to either downregulate BCR-ABL transcription or inhibit its tyrosine kinase activity.…”
Section: Gambogic Acidmentioning
confidence: 95%
“…The emergence of imatinib resistance in patients with CML les to the search for novel approaches for its treatment. Liu's group [71] has investigated the antineoplastic effects of GA in CML cell lines, mononuclear cells from CML patients and in imatinib-resistant xenograft murine models. The results indicated that GA induces apoptosis together with cell proliferation inhibition in CML cells, including those cells harboring the BCR-ABL-T315I mutation, and primary mononuclear cells from CML patients resistant to imatinib.…”
Section: Gambogic Acidmentioning
confidence: 99%
“…Pathways for induction of apoptosis have been identifiedintrinsic and extrinsic, one involving caspase-8 and the other involving Caspase-9 as the most apical caspase, which can activate effector caspase, such as Caspase-3, -6, -7. The effector caspases then cleave intracellular substrates, thereby important cellular processes are disabled and eventually cell death is caused [7][8][9].…”
Section: Apoptosis and Autophagymentioning
confidence: 99%